THE EFFECT OF CONSUMER FACTORS AND STORE IMAGE WHICH IS MODERATED BY PLB IMAGE TOWARDS PLB PURCHASE INTENTION - Maria Patricia Gautama; Jony Oktavian Haryanto (Journal of Management and Business, 2011)
Nowadays the development of Private Label Brands (PLBs) is increasing; this is proven by the increasing number of PLBs products in various product categories that we can found in several types of stores such as a supermarket, hypermarket format or in convenience store. PLBs have a very good opportunity in the market, considering many consumers are realizing that the price of PLBs which tend to be cheaper and with good qualities when compared with the price of national brands or product manufacturer. It also becomes interesting when it is known that the opportunities are widely open and it is proven with more and more retailers which aggressively producing PLBs. They give consumers more choices with a more affordable price but still provide good quality, especially in this world economy condition that tends to go down which of course also affect consumer purchasing power. By these reasons, the aim of the study is to determine whether the consumer and store image factors have a significant relationship in encouraging consumers to make PLB purchases, especially when it is moderated by PLB Image. The results showed that there are significant effect from consumer factors and stores image toward PLB purchase intention and its getting increase with the moderation of the PLB image.